2020
DOI: 10.1002/jtr.2402
|View full text |Cite
|
Sign up to set email alerts
|

Critical success factors for food tourism destinations: A socio‐cultural perspective

Abstract: Eating the food of other cultures is fraught with many problems underpinned by many factors chief among them being sociocultural background. The study, therefore, through a socio-cultural perspective, examines the factors necessary for food tourism development and promotion from tourists' perspectives. Using the tenets of grounded theory, 40 international tourists were interviewed at Cape Coast, Ghana. It was found that sensory characteristics and mediated by factors such as cultural/ worldviews influence loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 100 publications
1
14
0
Order By: Relevance
“…While this result may contradict the findings of studies in other contexts, the finding was somewhat expected based on the evidence offered by previous studies conducted in the local context. Earlier studies (Adongo et al , 2015; Hiamey et al , 2021) have confirmed the willingness of international tourists to consume local food in Ghana as part of their search for authentic experiences. However, concerns regarding the spiciness, perceived unwholesomeness and perceived susceptibility to illnesses have been identified as “inhibitors” of tourists’ local food consumption in Ghana (Amuquandoh, 2011; Adongo et al , 2015).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…While this result may contradict the findings of studies in other contexts, the finding was somewhat expected based on the evidence offered by previous studies conducted in the local context. Earlier studies (Adongo et al , 2015; Hiamey et al , 2021) have confirmed the willingness of international tourists to consume local food in Ghana as part of their search for authentic experiences. However, concerns regarding the spiciness, perceived unwholesomeness and perceived susceptibility to illnesses have been identified as “inhibitors” of tourists’ local food consumption in Ghana (Amuquandoh, 2011; Adongo et al , 2015).…”
Section: Discussionmentioning
confidence: 90%
“…The present paper, therefore, addresses the evident knowledge gap by applying the an attribute–benefit–value–intention (ABVI) framework, as an extension of the Stimulus-Organism-Response (SOR) theory, to international tourists’ local food consumption experiences in an indigenous African context. Within Africa, Ghana presents a suitable study setting as, in addition to its heritage attractions, it is known for its unique local gastronomy (Adongo et al , 2015; Hiamey et al , 2021; Kim et al , 2020) and is receiving an increasing number of tourists who have interests in local food exploration (Ghana Tourism Authority, 2019). Given that previous studies on tourists’ local food consumption have focused primarily on the West and the South-East Asian region, an African context expands this area of research, helping to understand the complexity of the global food tourism market.…”
Section: Introductionmentioning
confidence: 99%
“…Color, in addition to flavor and texture, is an essential factor in determining the sensory qualities of food products [ 41 ]. As a result, color is an important component of visual appearance, influencing and underpinning assumptions about the predicted smell and taste [ 42 ]. The presence of various ingredients used to make the oleogels governs their final coloration.…”
Section: Resultsmentioning
confidence: 99%
“…Fourth , Hiamey et al (2020) assessed the factors necessary for food tourism development and promotion from a tourist perspective based by deploying grounded theory and participant interviews. In doing so, the authors concluded that the socio‐cultural background of ‘the tourist’ affects their evaluation of a destination's food offering, and consumption enacted therein.…”
Section: Articles In This Issuementioning
confidence: 99%